2022
DOI: 10.3390/f13020335
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Vertical Structures, Thermal Comfort, Negative Air Ions, and Human Physiological Stress of Forest Walking Spaces in Summer

Abstract: Forest walking is a popular, healthy, and light outdoor activity. The potential comprehensive relationships between the vertical structures, thermal comfort, negative air ions (NAI), and human physiological stress in forest walking spaces have not been determined. We performed an experiment in the Baishuihe National Nature Reserve, Sichuan Province, China. Thirty-two college students recruited as subjects completed a forest walk (approximately one kilometer) on the same trail divided into three vertical struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Human thermal comfort and recreation climatology [79,80], "biophobia"-fear of nature and insects [81,82] Accessibility-getting to and using the site Proximity Distance/travel time from "home" or population centers "Develop trails close to where people live for easier access" (5). "For a lot of people it is an edge to come out on one of these walks and .…”
Section: Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Human thermal comfort and recreation climatology [79,80], "biophobia"-fear of nature and insects [81,82] Accessibility-getting to and using the site Proximity Distance/travel time from "home" or population centers "Develop trails close to where people live for easier access" (5). "For a lot of people it is an edge to come out on one of these walks and .…”
Section: Integritymentioning
confidence: 99%
“…In our previous review of the forest therapy literature [22], the few studies examining microclimatic factors generally found that measures such as high air temperatures and relative humidity can negatively impact physiological and psychological health outcomes [171][172][173]. Notably, Lin et al [80] developed a thermal comfort model to identify the optimal structural conditions and times of day for forest walks. A growing focus of recreation climatology has examined the impact of climate change on nature-based activities [174][175][176], including those dependent on a narrow range of environmental conditions such as snow for skiing [177,178], as well as how increased pollinosis [179,180], the spread of disease-transmitting insects [181][182][183], and other concerns can pose challenges for people seeking a comfortable experience in nature.…”
Section: Environmentalmentioning
confidence: 99%
“…Additionally, with respect to location, studies were set in rural (n = 105, 45.1%) [83,139], urban (n = 89, 38.2%) [84,140], mixed rural-urban (n = 25, 10.7%) [141,142], or were virtual studies without a specified location (n = 14, 6.0%) [143,144]. Along with these broad categorizations, the settings of 54 studies were identified as designated forest bathing or forest therapy sites, mainly in Japan [145,146], South Korea [108,111], and China [63,147].…”
Section: Overall Forest Characteristics Studiedmentioning
confidence: 99%
“…NAIs offer various psychological and physiological benefits to the human body, including stress reduction [3], enhancement of cardiovascular function [4], and improvement of cognitive abilities [5]. Animal experiments [6,7] and human studies investigating both physiological and psychological health [3,8] have confirmed NAIs' effectiveness as supplementary treatment methods for a wide range of diseases. Furthermore, NAIs contribute to air purification and dust adsorption, playing a crucial role in maintaining environmental cleanliness levels [9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…They are specifically called negative oxygen ions due to oxygen's exceptional ability to capture free electrons and its inherent inclination to acquire them [1,2]. NAIs offer various psychological and physiological benefits to the human body, including stress reduction [3], enhancement of cardiovascular function [4], and improvement of cognitive abilities [5]. Animal experiments [6,7] and human studies investigating both physiological and psychological health [3,8] have confirmed NAIs' effectiveness as supplementary treatment methods for a wide range of diseases.…”
Section: Introductionmentioning
confidence: 99%